Implementation of Good Governance Principles in Public Services - Meilasari, Indah; Haryaningsih, Sri; Maryuni, Sri (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This research provides an understanding of the implementation of good governance principles in the public service at the Class IIA Correctional Facility Pontianak. The research investigates issues related to the occurrence of overcrowding for years in the correctional facility, the lack of prison guards responsible for family visit services, and the baggage scanner (X-ray machine) for family visitors that is already broken. The purpose of this research is to describe and analyze how good governance principles are implemented in the public service at the Class IIA Correctional Facility Pontianak. The results showed that the correctional facility implemented at least two of nine principles expressed by the UNDP 1997, such as the responsiveness principle and efficient and effectiveness principle. Based on the interviews and observations in this research, prison guards have served visitors responsively, in line with the SOP. The prison guards strive to maintain a high level of accuracy in their work, although the shortage of service staff remains an obstacle to providing responsive services. Meanwhile, in the efficient and effective principle, the research observed that the service was given structurally. However, the visit baggage scanning was still low due to the limited number of prison guards and the large number of visitor belongings while visiting the correctional facility. This research suggests that an implementation of virtual reality (VR) -based visits to facilitate families who live far from the correctional facility. In addition, the use of big data and AI is highly encouraged to manage visitor load and develop a “Visit Facilitator” program involving the alumni of the prisoners or some volunteers. As a final suggestion, a gamification system is needed to improve compliance with visitation procedures, along with mobile visitation services through a mobile service unit.